Penurunan Nyeri Pada Arthritis Gout Melalui Kompres Hangat Air Rebusan Serai: The Reduction of Gout Arthritis Pain with Warm Compress of Boiled Lemon Grass - Dewi Siti Oktavianti; Siti Anzani (Madago Nursing Journal, 2021)
Introduction: Gout arthritis is a type of arthritis that caused too much uric acid in the blood and accumulation of uric acid crystals and causing pain. This pain will interfere with activities. The study aims to determine the effect of warm compresses of Boiled lemon Grass reduce the intensity pain of gout. Method: This research used Quasi Experiment design, pre-test and post-test without control. The research samples were 20 respondents who feel pain gout arthritis and have increased levels of uric acid in the blood. The instruments used were the observation sheet and pain intensity scale measurement sheet with Numeric Rating Scale (NRS). The statistical test used the Paired T Test. Results: The results showed that differences in the pain intensity before and after intervention with p value 0.005, meaning there was a significant effect warm compressed of Boiled lemon Grass to reduce pain in Gout arthritis. Conclusion: The warm compresses of Boiled lemon Grass can be used as a non-pharmacological therapy to reduce the pain of gout arthritis.